Question
upstudy study bank question image url

each given function \( f(x) \) : Draw the graphs of \( f(x) \) and its inverse on the same set of axes. Clearly show all the intercepts with the axes, asymptotes and lines of symmetry. Write the equation of the inverse of \( f(x) \) in the form \( y=\ldots \) \( f(x)=\frac{1}{(x+2)}+3 \) \( f(x)=(x-3)^{2}-1 \) \( f(x)=\frac{-2}{(x-4)}+2 \) \( f(x)=-(x+4)^{2}+1 \)

Ask by Warner Long. in South Africa
Feb 19,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

To find the inverses of the given functions, swap \( x \) and \( y \) and solve for \( y \). The inverses are: 1. \( f^{-1}(x) = \frac{7 - 2x}{x - 3} \) 2. \( f^{-1}(x) = 3 \pm \sqrt{1+x} \) 3. \( f^{-1}(x) = \frac{-10 + 4x}{x - 2} \) 4. \( f^{-1}(x) = -4 \pm \sqrt{1+x} \) Graphs of each function and its inverse can be plotted by identifying intercepts and asymptotes, then reflecting the function over the line \( y = x \).

Solution

Function by following steps: - step0: Find the y-intercept: \(f\left(x\right)=x^{2}-6x+8\) - step1: Set \(x\)=0\(:\) \(f\left(0\right)=0^{2}-6\times 0+8\) - step2: Multiply: \(f\left(0\right)=0^{2}-0+8\) - step3: Simplify: \(f\left(0\right)=8\) Analyze the y intercept of the function \( f(x)=-(x+4)^{2}+1 \) Function by following steps: - step0: Find the y-intercept: \(f\left(x\right)=-x^{2}-8x-15\) - step1: Set \(x\)=0\(:\) \(f\left(0\right)=-0^{2}-8\times 0-15\) - step2: Multiply: \(f\left(0\right)=-0^{2}-0-15\) - step3: Simplify: \(f\left(0\right)=-15\) Analyze the y intercept of the function \( f(x)=\frac{-2}{(x-4)}+2 \) Function by following steps: - step0: Find the y-intercept: \(f\left(x\right)=-\frac{2}{x-4}+2\) - step1: Set \(x\)=0\(:\) \(f\left(0\right)=-\frac{2}{0-4}+2\) - step2: Simplify: \(f\left(0\right)=\frac{5}{2}\) Analyze the y intercept of the function \( f(x)=\frac{1}{(x+2)}+3 \) Function by following steps: - step0: Find the y-intercept: \(f\left(x\right)=\frac{1}{x+2}+3\) - step1: Set \(x\)=0\(:\) \(f\left(0\right)=\frac{1}{0+2}+3\) - step2: Simplify: \(f\left(0\right)=\frac{7}{2}\) Analyze the x intercept of the function \( f(x)=\frac{1}{(x+2)}+3 \) Function by following steps: - step0: Find the \(x\)-intercept/zero: \(f\left(x\right)=\frac{1}{x+2}+3\) - step1: Set \(f\left(x\right)\)=0\(:\) \(0=\frac{1}{x+2}+3\) - step2: Swap the sides: \(\frac{1}{x+2}+3=0\) - step3: Find the domain: \(\frac{1}{x+2}+3=0,x\neq -2\) - step4: Move the constant to the right side: \(\frac{1}{x+2}=0-3\) - step5: Remove 0: \(\frac{1}{x+2}=-3\) - step6: Cross multiply: \(1=\left(x+2\right)\left(-3\right)\) - step7: Simplify the equation: \(1=-3\left(x+2\right)\) - step8: Swap the sides: \(-3\left(x+2\right)=1\) - step9: Change the signs: \(3\left(x+2\right)=-1\) - step10: Divide both sides: \(\frac{3\left(x+2\right)}{3}=\frac{-1}{3}\) - step11: Divide the numbers: \(x+2=-\frac{1}{3}\) - step12: Move the constant to the right side: \(x=-\frac{1}{3}-2\) - step13: Subtract the numbers: \(x=-\frac{7}{3}\) - step14: Check if the solution is in the defined range: \(x=-\frac{7}{3},x\neq -2\) - step15: Find the intersection: \(x=-\frac{7}{3}\) Analyze the x intercept of the function \( f(x)=-(x+4)^{2}+1 \) Function by following steps: - step0: Find the \(x\)-intercept/zero: \(f\left(x\right)=-x^{2}-8x-15\) - step1: Set \(f\left(x\right)\)=0\(:\) \(0=-x^{2}-8x-15\) - step2: Swap the sides: \(-x^{2}-8x-15=0\) - step3: Factor the expression: \(-\left(x+3\right)\left(x+5\right)=0\) - step4: Divide the terms: \(\left(x+3\right)\left(x+5\right)=0\) - step5: Separate into possible cases: \(\begin{align}&x+3=0\\&x+5=0\end{align}\) - step6: Solve the equation: \(\begin{align}&x=-3\\&x=-5\end{align}\) - step7: Calculate: \(x_{1}=-5,x_{2}=-3\) Analyze the x intercept of the function \( f(x)=\frac{-2}{(x-4)}+2 \) Function by following steps: - step0: Find the \(x\)-intercept/zero: \(f\left(x\right)=-\frac{2}{x-4}+2\) - step1: Set \(f\left(x\right)\)=0\(:\) \(0=-\frac{2}{x-4}+2\) - step2: Swap the sides: \(-\frac{2}{x-4}+2=0\) - step3: Find the domain: \(-\frac{2}{x-4}+2=0,x\neq 4\) - step4: Move the constant to the right side: \(-\frac{2}{x-4}=0-2\) - step5: Remove 0: \(-\frac{2}{x-4}=-2\) - step6: Rewrite the expression: \(\frac{-2}{x-4}=-2\) - step7: Cross multiply: \(-2=\left(x-4\right)\left(-2\right)\) - step8: Simplify the equation: \(-2=-2\left(x-4\right)\) - step9: Evaluate: \(1=x-4\) - step10: Swap the sides: \(x-4=1\) - step11: Move the constant to the right side: \(x=1+4\) - step12: Add the numbers: \(x=5\) - step13: Check if the solution is in the defined range: \(x=5,x\neq 4\) - step14: Find the intersection: \(x=5\) Analyze the x intercept of the function \( f(x)=(x-3)^{2}-1 \) Function by following steps: - step0: Find the \(x\)-intercept/zero: \(f\left(x\right)=x^{2}-6x+8\) - step1: Set \(f\left(x\right)\)=0\(:\) \(0=x^{2}-6x+8\) - step2: Swap the sides: \(x^{2}-6x+8=0\) - step3: Factor the expression: \(\left(x-4\right)\left(x-2\right)=0\) - step4: Separate into possible cases: \(\begin{align}&x-4=0\\&x-2=0\end{align}\) - step5: Solve the equation: \(\begin{align}&x=4\\&x=2\end{align}\) - step6: Calculate: \(x_{1}=2,x_{2}=4\) Solve the equation \( y=-(x+4)^{2}+1 \). Solve the equation by following steps: - step0: Solve for \(x\): \(y=-x^{2}-8x-15\) - step1: Swap the sides: \(-x^{2}-8x-15=y\) - step2: Move the expression to the left side: \(-x^{2}-8x-15-y=0\) - step3: Multiply both sides: \(x^{2}+8x+15+y=0\) - step4: Solve using the quadratic formula: \(x=\frac{-8\pm \sqrt{8^{2}-4\left(15+y\right)}}{2}\) - step5: Simplify the expression: \(x=\frac{-8\pm \sqrt{4-4y}}{2}\) - step6: Simplify the expression: \(x=\frac{-8\pm 2\sqrt{1-y}}{2}\) - step7: Separate into possible cases: \(\begin{align}&x=\frac{-8+2\sqrt{1-y}}{2}\\&x=\frac{-8-2\sqrt{1-y}}{2}\end{align}\) - step8: Simplify the expression: \(\begin{align}&x=-4+\sqrt{1-y}\\&x=\frac{-8-2\sqrt{1-y}}{2}\end{align}\) - step9: Simplify the expression: \(\begin{align}&x=-4+\sqrt{1-y}\\&x=-4-\sqrt{1-y}\end{align}\) Solve the equation \( y=(x-3)^{2}-1 \). Solve the equation by following steps: - step0: Solve for \(x\): \(y=x^{2}-6x+8\) - step1: Swap the sides: \(x^{2}-6x+8=y\) - step2: Move the expression to the left side: \(x^{2}-6x+8-y=0\) - step3: Solve using the quadratic formula: \(x=\frac{6\pm \sqrt{\left(-6\right)^{2}-4\left(8-y\right)}}{2}\) - step4: Simplify the expression: \(x=\frac{6\pm \sqrt{4+4y}}{2}\) - step5: Simplify the expression: \(x=\frac{6\pm 2\sqrt{1+y}}{2}\) - step6: Separate into possible cases: \(\begin{align}&x=\frac{6+2\sqrt{1+y}}{2}\\&x=\frac{6-2\sqrt{1+y}}{2}\end{align}\) - step7: Simplify the expression: \(\begin{align}&x=3+\sqrt{1+y}\\&x=\frac{6-2\sqrt{1+y}}{2}\end{align}\) - step8: Simplify the expression: \(\begin{align}&x=3+\sqrt{1+y}\\&x=3-\sqrt{1+y}\end{align}\) Solve the equation \( y=\frac{-2}{(x-4)}+2 \). Solve the equation by following steps: - step0: Solve for \(x\): \(y=-\frac{2}{x-4}+2\) - step1: Swap the sides: \(-\frac{2}{x-4}+2=y\) - step2: Move the constant to the right side: \(-\frac{2}{x-4}=y-2\) - step3: Multiply both sides of the equation by LCD: \(-\frac{2}{x-4}\times \left(x-4\right)=\left(y-2\right)\left(x-4\right)\) - step4: Simplify the equation: \(-2=\left(y-2\right)x-4y+8\) - step5: Swap the sides: \(\left(y-2\right)x-4y+8=-2\) - step6: Move the constant to the right side: \(\left(y-2\right)x=-2+4y-8\) - step7: Subtract the numbers: \(\left(y-2\right)x=-10+4y\) - step8: Divide both sides: \(\frac{\left(y-2\right)x}{y-2}=\frac{-10+4y}{y-2}\) - step9: Divide the numbers: \(x=\frac{-10+4y}{y-2}\) Solve the equation \( y=\frac{1}{(x+2)}+3 \). Solve the equation by following steps: - step0: Solve for \(x\): \(y=\frac{1}{x+2}+3\) - step1: Swap the sides: \(\frac{1}{x+2}+3=y\) - step2: Move the constant to the right side: \(\frac{1}{x+2}=y-3\) - step3: Multiply both sides of the equation by LCD: \(\frac{1}{x+2}\times \left(x+2\right)=\left(y-3\right)\left(x+2\right)\) - step4: Simplify the equation: \(1=\left(y-3\right)x+2y-6\) - step5: Swap the sides: \(\left(y-3\right)x+2y-6=1\) - step6: Move the constant to the right side: \(\left(y-3\right)x=1-\left(2y-6\right)\) - step7: Subtract the terms: \(\left(y-3\right)x=7-2y\) - step8: Divide both sides: \(\frac{\left(y-3\right)x}{y-3}=\frac{7-2y}{y-3}\) - step9: Divide the numbers: \(x=\frac{7-2y}{y-3}\) Let's analyze each function \( f(x) \) step by step, including finding the intercepts, asymptotes, and the equations of their inverses. ### 1. Function: \( f(x) = \frac{1}{(x+2)} + 3 \) **Intercepts:** - **X-intercept:** Set \( f(x) = 0 \): \[ 0 = \frac{1}{(x+2)} + 3 \implies x = -\frac{7}{3} \] - **Y-intercept:** Set \( x = 0 \): \[ f(0) = \frac{1}{(0+2)} + 3 = \frac{1}{2} + 3 = \frac{7}{2} \text{ or } 3.5 \] **Asymptotes:** - Vertical asymptote at \( x = -2 \) (where the denominator is zero). **Inverse:** To find the inverse, swap \( x \) and \( y \): \[ y = \frac{1}{(x+2)} + 3 \implies x = \frac{1}{(y+2)} + 3 \implies y = \frac{7 - 2x}{x - 3} \] ### 2. Function: \( f(x) = (x-3)^{2} - 1 \) **Intercepts:** - **X-intercepts:** Set \( f(x) = 0 \): \[ 0 = (x-3)^{2} - 1 \implies x = 2, 4 \] - **Y-intercept:** Set \( x = 0 \): \[ f(0) = (0-3)^{2} - 1 = 9 - 1 = 8 \] **Asymptotes:** - No vertical or horizontal asymptotes. **Inverse:** To find the inverse, swap \( x \) and \( y \): \[ y = (x-3)^{2} - 1 \implies x = (y-3)^{2} - 1 \implies y = 3 + \sqrt{1+y} \text{ or } y = 3 - \sqrt{1+y} \] ### 3. Function: \( f(x) = \frac{-2}{(x-4)} + 2 \) **Intercepts:** - **X-intercept:** Set \( f(x) = 0 \): \[ 0 = \frac{-2}{(x-4)} + 2 \implies x = 5 \] - **Y-intercept:** Set \( x = 0 \): \[ f(0) = \frac{-2}{(0-4)} + 2 = \frac{1}{2} + 2 = \frac{5}{2} \text{ or } 2.5 \] **Asymptotes:** - Vertical asymptote at \( x = 4 \). **Inverse:** To find the inverse, swap \( x \) and \( y \): \[ y = \frac{-2}{(x-4)} + 2 \implies x = \frac{-2}{(y-4)} + 2 \implies y = \frac{-10 + 4x}{x - 2} \] ### 4. Function: \( f(x) = -(x+4)^{2} + 1 \) **Intercepts:** - **X-intercepts:** Set \( f(x) = 0 \): \[ 0 = -(x+4)^{2} + 1 \implies x = -5, -3 \] - **Y-intercept:** Set \( x = 0 \): \[ f(0) = -(0+4)^{2} + 1 = -16 + 1 = -15 \] **Asymptotes:** - No vertical or horizontal asymptotes. **Inverse:** To find the inverse, swap \( x \) and \( y \): \[ y = -(x+4)^{2} + 1 \implies x = -(y+4)^{2} + 1 \implies y = -4 + \sqrt{1-y} \text{ or } y = -4 - \sqrt{1-y} \] ### Summary of Inverses 1. \( f^{-1}(x) = \frac{7 - 2x}{x - 3} \) 2. \( f^{-1}(x) = 3 \pm \sqrt{1+x} \) 3. \( f^{-1}(x) = \frac{-10 + 4x}{x - 2} \) 4. \( f^{-1}(x) = -4 \pm \sqrt{1+x} \) ### Graphing To graph these functions and their inverses, plot the functions along with their intercepts and asymptotes. The line \( y = x \) will serve as the line of symmetry for the function and its inverse. If you need the actual graphs plotted, please let me know!

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To analyze the functions and their inverses, we can look at each function one by one. 1. **Function**: \( f(x) = \frac{1}{(x+2)} + 3 \) - **Graph**: This function has a vertical asymptote at \( x = -2 \) and a horizontal asymptote at \( y = 3 \). The y-intercept occurs when \( x = 0 \), giving \( f(0) = \frac{1}{2} + 3 = 3.5 \). - **Inverse**: To find the inverse, switch \( x \) and \( y \) and solve for \( y \): \[ x = \frac{1}{(y+2)} + 3 \Rightarrow y = \frac{1}{(x-3)} - 2. \] Thus, the inverse is \( y = \frac{1}{(x-3)} - 2 \). 2. **Function**: \( f(x) = (x-3)^2 - 1 \) - **Graph**: This is a parabola opening upwards with its vertex at \( (3, -1) \). The y-intercept occurs when \( x = 0 \), giving \( f(0) = 8 \). The axis of symmetry is \( x = 3 \). - **Inverse**: To find the inverse, solve for \( y \): \[ y + 1 = (x-3)^2 \Rightarrow x-3 = \pm\sqrt{y+1} \Rightarrow x = 3 \pm \sqrt{y + 1}. \] The main branch of the inverse is \( y = (x - 3)^2 - 1 \). 3. **Function**: \( f(x) = \frac{-2}{(x-4)} + 2 \) - **Graph**: This function has a vertical asymptote at \( x = 4 \) and a horizontal asymptote at \( y = 2 \). The y-intercept is found giving \( f(0) = -\frac{1}{2} + 2 = 1.5 \). - **Inverse**: Solve for \( y \): \[ x - 2 = \frac{-2}{(y-4)} \Rightarrow (y-4)(x-2) = -2. \] Thus the inverse is \( y = \frac{-2}{(x-2)} + 4 \). 4. **Function**: \( f(x) = -(x+4)^2 + 1 \) - **Graph**: This is a downward-opening parabola with a vertex at \( (-4, 1) \). The y-intercept occurs when \( x = 0 \), yielding \( f(0) = -16 + 1 = -15 \). The axis of symmetry is \( x = -4 \). - **Inverse**: To find the inverse: \[ y - 1 = -(x + 4)^2 \Rightarrow -(x + 4)^2 = y-1 \Rightarrow x + 4 = \pm\sqrt{1 - y} \Rightarrow x = -4 \pm \sqrt{1 - y}. \] The main branch of the inverse can be expressed as \( y = -\sqrt{1 - x} - 4 \). ### Summary of Inverses: 1. \( y = \frac{1}{(x-3)} - 2 \) 2. \( y = \sqrt{x + 1} + 3 \) (main branch of the square root taken) 3. \( y = \frac{-2}{(x-2)} + 4 \) 4. \( y = -\sqrt{1 - x} - 4 \) (main branch taken)

Latest Pre Calculus Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy